Characterization of gliclazide-polyethylene glycol solid dispersion and its effect on dissolution - Moreshwar Pandharinath Patil; Naresh Janardan Gaikwad (Universidade de São Paulo, 2011)
The present study was initiated with the objective of studying the in vitro dissolution behavior of gliclazide from its solid dispersion with polyethylene glycol 6000. In this work, a solid dispersion of gliclazide with polyethylene glycol was prepared by the fusion method. In vitro dissolution study of gliclazide, its physical mixture and solid dispersion were carried out to demonstrate the effect of PEG 6000. Analytical techniques of FT-IR spectroscopy, differential scanning calorimetry and X-ray diffractometry were used to characterize the drug in the physical mixtures and solid dispersions. The dissolution studies of solid dispersion and physical mixture showed greater improvement compared to that of the pure drug. The mechanisms for increased dissolution rate may include reduction of crystallite size, a solubilization effect of the carrier, absence of aggregation of drug crystallites, improved wettability and dispersbility of the drug from the dispersion, dissolution of the drug in the hydrophilic carrier or conversion of drug to an amorphous state. The FT-IR spectra suggested that there was no interaction between gliclazide and PEG 6000 when prepared as a solid dispersion. DSC and XRD study indicated that the drug was converted in the amorphous form. O presente trabalho foi realizado com o objetivo de estudar o comportamento in vitro da dissolução da gliclazida a partir da sua dispersão sólida com polietileno glicol 6000. Neste trabalho, as dispersões sólidas de gliclazida com polietileno glicol foram preparadas pelo método de fusão. Os estudo de dissolução in vitro da gliclazida, na mistura física e nas dispersões sólidas foram realizados para demonstrar o efeito de PEG 6000. Técnicas analíticas como espectroscopia FT-IR, calorimetria diferencial de varredura e difração de raios-X foram empregadas para caracterizar o fármaco nas misturas físicas e nas dispersoes sólidas. Os estudos de dissolução demonstraram maior melhoria. Os mecanismos para aumentar a velocidade de dissolução podem incluir a redução do tamanho dos cristais, a solubilização do carreador, a ausência de agregação dos cristais do fármaco, a melhoria da molhabilidade e dispersibilidade do fármaco a partir da dispersão, a dissolução do fármaco no carreador hidrofílico ou conversão da forma cristalina do fármaco para estado amorfo. Os espectros de FT-IR sugeriram que não houve interação entre gliclazide PEG 6000 e na sua combinação. Os estudos de DSC e DRX indicaram que o fármaco foi convertido para a forma amorfa.